Lost and found voices : four gay male writers in exile - Beaudoin, Luc J. (McGill-Queen's University Press, 2022)
"One writer is stranded by the Second World War. Another flees multiple revolutions to live the rest of his life in Rio de Janeiro. Two others, public about their sexuality at home, choose self-exile. In Lost and Found Voices Luc Beaudoin offers a critical engagement with these four displaced authors: Witold Gombrowicz, Valerii Pereleshin, Abdellah Taïa, and Slava Mogutin. Not quite fitting into their respective diasporas and sharing an urge to express their queer desires, it is in their published works of literature, film, and photography that these writers locate their shifting identities and emergent queer voices. Their artistry is the basis from which Beaudoin traces their expressions of desire in language, culture, and community, offering a contextual queer reading that navigates their linguistic, cultural, artistic, and sexual self-translations and self-portrayals. Their choices are determinative: Gombrowicz masked his attraction to men in his works, keeping the truth hidden in an intimate diary; Pereleshin explored his lust in Brazilian Portuguese after being shunned by the Russian diaspora; Taïa writes in French to destabilize both the language and his status as an immigrant in France; Mogutin becomes a hardcore gay rebel in word and image to rattle assumptions about gay life. Bringing authors generally not familiar to an English-speaking readership into one volume, and including Beaudoin's own experience of living between languages, Lost and Found Voices provides provocative insights into what it means to be gay in both the past and the present."--